FROM PERSONALIZED TO PRECISION MEDICINE - K. V. Raskina; E. Y. Martynova; A. V. Perfilyev; D. A. Sychev; G. N. Shuev; I. R. Fatkhutdinov; S. V. Musienko; D. A. Nikogosov; I. O. Zhegulina; L. G. Bavykina; Y. E. Poteshkin (Рациональная фармакотерапия в кардиологии)
The need to maintain a high quality of life against a backdrop of its inevitably increasing duration is one of the main problems of modern health care. The concept of "right drug to the right patient at the right time", which at first was bearing the name "personalized", is currently unanimously approved by international scientific community as "precision medicine". Precision medicine takes all the individual characteristics into account: genes diversity, environment, lifestyles, and even bacterial microflora and also involves the use of the latest technological developments, which serves to ensure that each patient gets assistance fitting his state best. In the United States, Canada and France national precision medicine programs have already been submitted and implemented. The aim of this review is to describe the dynamic integration of precision medicine methods into routine medical practice and life of modern society. The new paradigm prospects description are complemented by figures, proving the already achieved success in the application of precise methods for example, the targeted therapy of cancer. All in all, the presence of real-life examples, proving the regularity of transition to a new paradigm, and a wide range  of technical and diagnostic capabilities available and constantly evolving make the all-round transition to precision medicine almost inevitable.